Taxonomic revision of Wissadula (Malvoideae, Malvaceae) in Brazil - Bovini, Massimo Giuseppe; Baumgratz, José Fernando A. (Phytotaxa, 2016)
A comprehensive taxonomic revision of the genus Wissadula (Malvoideae, Malvaceae) in Brazil is presented. Through field surveys, examination of the specimens maintained in 39 herbaria, and a review of the literature, 19 Wissadula species are recognized. The main diagnostic characteristics used to distinguish amonth species are leaf shape, trichome type on branches and leaves, and the shape and number of mericarps. Wissadula mainly differs from the other genera in Malvoideae in having a mericarp constriction. A diagnostic key, detailed descriptions, illustrations, and geographic data are provided. Three species (W. boliviana, W. wissadifolia, and W. setifera) are recorded for the first time in Brazil. New synonyms and the typification of some names are also proposed, including for the Wissadula section Wissadula. Seven species are illustrated for the first time. Phytogeographic data suggest a neotropical distribution for this genus, with high species diversity in Paraguay, northern Argentina, eastern Bolivia, and western Brazil.